Vanadium-based positive electrode material, preparation method thereof and zinc battery

The vanadium-based positive electrode material of imidazole ion intercalation was prepared by a one-pot stirring method, which solved the problem of rapid decline in the vanadium-based positive electrode capacity of zinc batteries, and achieved high capacity and stable circulation performance.

CN119890282APending Publication Date: 2025-04-25GANTRY LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411951100.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The vanadium-based positive electrode of zinc battery is prone to collapse during the battery charging and discharge cycle, and the dissolution of vanadium oxides leads to a rapid decline in battery capacity and hinders the development of vanadium-based positive electrode of zinc battery.

Method used

The vanadium-based positive electrode material of imidazole ion intercalation is prepared by a one-pot stirring method, using the functional groups of imidazole ions to provide more zinc ion intercalation sites, stabilize the layered structure, reduce electrostatic effects, and promote zinc ion diffusion.

Benefits of technology

The high capacity, capacity retention rate and electrochemical kinetic performance of vanadium-based cathode materials have been improved, which extends the cycle stability of the battery and reduces the capacity attenuation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890282A_ABST
    Figure CN119890282A_ABST
Patent Text Reader

Abstract

The invention provides a vanadium-based positive electrode material, a preparation method thereof and a zinc battery, and the preparation method of the vanadium-based positive electrode material comprises the following steps: putting commercial vanadium pentoxide powder into a beaker, and adding deionized water; then adding imidazole chloride into the beaker; then adding magnetons into the beaker, and magnetically stirring uniformly to obtain a mixture; and filtering the mixture, collecting a solid, and fully drying the solid to obtain the vanadium-based positive electrode material. The imidazole-ion-intercalated vanadium-based positive electrode material is successfully prepared through a one-pot stirring method, the adopted method can achieve large-scale production and has the advantages of being simple, low in production cost and the like, and the obtained imidazole-intercalated vanadium-based positive electrode material has the advantages of being large in specific surface area, uniform in morphology, stable in structure and the like; more zinc ion embedding sites can be provided, a layered structure is supported, and long-term stable circulation of the battery is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc battery positive electrode materials, in particular to a vanadium-based positive electrode material and a preparation method thereof, and a zinc battery. Background Art

[0002] As energy demand increases year by year, the reserves of non-renewable energy such as fossil energy decrease year by year, so the problem of renewable energy use needs to be solved. Electrochemical energy storage is a good way to utilize renewable energy, so people have been exploring the development and utilization of various batteries. At present, lithium-ion batteries have been successfully commercialized, but they still face problems such as flammability. Sodium ion, potassium ion, zinc ion batteries, etc. have also received attention. Among them, aqueous zinc batteries have high safety and high volumetric capacity (5855 mAh cm −3 ) and a relatively low redox potential (−0.76 V vs standard hydrogen), showing great development potential. Vanadium-based materials have open structures and multivalent states, and are one of the candidates for positive electrode materials for zinc-ion batteries. However, due to the easy collapse of the layered structure of vanadium-based positive electrodes and the dissolution of vanadium oxides during the battery charge and discharge cycle, the battery capacity decreases rapidly, which hinders the development of vanadium-based positive electrodes for zinc batteries.

[0003] To solve the above problems, people have adopted many strategies including ion pre-intercalation, construction of positive electrode protective layer, and optimization of electrolyte components. Among them, ion pre-intercalation has the advantages of expanding the interlayer spacing of vanadium oxide and stabilizing the layer structure, which can improve the capacity and capacity retention rate of zinc battery positive electrode. For example: pre-intercalating potassium ions and aluminum ions into vanadium pentoxide by hydrothermal method to obtain higher capacity and better positive electrode stability. These strategies provide ideas and construction methods for constructing vanadium-based positive electrodes for zinc batteries, but the hydrothermal method has high requirements for large-scale production, and the modification method of vanadium-based positive electrodes still needs to be explored.

[0004] Therefore, a simple and scalable method for preparing vanadium-based positive electrode materials is needed to solve the problem of rapid capacity decay of vanadium-based positive electrodes in zinc batteries and increase battery capacity. Summary of the invention

[0005] In order to address the deficiencies in the prior art, the present invention provides a vanadium-based positive electrode material and a preparation method thereof, and a zinc battery. The present invention successfully prepares an imidazolium ion intercalated vanadium-based positive electrode material through a one-pot stirring method. The adopted method can realize large-scale production and has the advantages of simple method and low production cost. The obtained imidazolium intercalated vanadium-based positive electrode material has the advantages of large specific surface area, uniform morphology, stable structure, etc., can provide more zinc ion embedding sites, support the layered structure, and realize long-term stable battery circulation.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: On the one hand, the present invention discloses a method for preparing a vanadium-based positive electrode material, which mainly comprises the following steps: Step (1), placing commercial vanadium pentoxide powder in a beaker, and adding deionized water; Step (2), taking imidazole chloride and adding it into the beaker of step (1); Step (3), adding a magnet to the beaker, and stirring evenly by magnetic force to obtain a mixture; Step (4), filtering the mixture, collecting the solid, and fully drying the solid to obtain a vanadium-based positive electrode material.

[0007] Furthermore, in step (1), the purity of the commercial vanadium pentoxide powder is not less than 99%.

[0008] Furthermore, in step (2), the purity of the imidazole chloride is not less than 98%.

[0009] Furthermore, in step (2), the imidazole chloride includes any one or more of 1,3-dimethyl imidazole chloride, 1-methyl-3-ethyl imidazole chloride, and 1-methyl-3-propyl imidazole chloride.

[0010] Furthermore, the concentration of vanadium pentoxide in the product obtained in step (1) is 60-70 g / L.

[0011] Furthermore, the concentration of imidazole chloride in the product obtained in step (2) is 0.5-2 mol / L.

[0012] Furthermore, in step (3), the stirring speed of the magnetic stirring is 600-1000 r / min, and the stirring time is 4 days.

[0013] Furthermore, in step (4), vacuum drying is performed at a temperature of 50-70° C. for 1 day.

[0014] On the other hand, the present invention discloses a vanadium-based positive electrode material, which is prepared by the above method.

[0015] In another aspect, the present invention discloses a zinc battery comprising the above-mentioned vanadium-based positive electrode material.

[0016] Beneficial effects: The present invention obtains an imidazole intercalated vanadium-based positive electrode material by a one-pot stirring method. The material presents a nanowire morphology, has a higher specific surface area, and can fully contact with an electrolyte; has a wider interlayer spacing, and the functional groups in the imidazole ions can provide more zinc ions to embed into active sites, thereby achieving high capacity; the positively charged imidazole ions can reduce the electrostatic interaction between vanadium pentoxide layers and promote the diffusion of zinc ions; the imidazole ions can stabilize the layered structure and prevent the structural collapse of the vanadium-based layered material, so that the vanadium-based zinc positive electrode can stably circulate during the charge and discharge process, thereby improving the battery capacity, capacity retention rate and electrochemical kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the XRD pattern of the product obtained in Example 1.

[0018] Figure 2 The following are scanning electron microscope images of the products obtained in Examples 1-3 and vanadium pentoxide.

[0019] Figure 3 This is the distribution diagram of all elements of the product obtained in Example 1.

[0020] Figure 4 This is the distribution diagram of various elements of the product obtained in Example 1.

[0021] Figure 5 The following is the Fourier transform infrared spectrum of the product obtained in Example 1.

[0022] Figure 6 This is a charge and discharge cycle test diagram of a full battery assembled from the product obtained in Example 1.

[0023] Figure 7 This is the cyclic voltammetry curve of the full battery assembled with the product obtained in Example 1. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Example 1 This embodiment provides a method for preparing a vanadium-based positive electrode material, which mainly includes the following steps: Step (1), weigh 2 g of vanadium pentoxide powder, place it in a 50 ml beaker, and add 30 ml of deionized water to the beaker; Step (2), weigh 4.4 g of 1-ethyl-3-methylimidazolium chloride and add it to a beaker. The concentration of 1-ethyl-3-methylimidazolium chloride in the obtained product is 1 mol / L; Step (3), adding a magnet of appropriate size into the beaker, setting the rotation speed to 800 r / min, and stirring for 4 days to obtain a mixture; Step (4), filtering the mixture and washing it three times with deionized water, collecting the solid insoluble matter, and drying the solid insoluble matter in a vacuum drying oven at 60° C. for 24 hours to obtain an imidazole intercalated vanadium-based positive electrode material.

[0026] Example 2 The only difference between Example 2 and Example 1 is that in step (2), 2.2 g of 1-ethyl-3-methylimidazolium chloride is weighed and added to a beaker, and the concentration of 1-ethyl-3-methylimidazolium chloride in the obtained product is 0.5 mol / L.

[0027] Example 3 The only difference between Example 3 and Example 1 is that in step (2), 8.8 g of 1-ethyl-3-methylimidazolium chloride is weighed and added to a beaker, and the concentration of 1-ethyl-3-methylimidazolium chloride in the obtained product is 2 mol / L.

[0028] The products obtained in Examples 1-3 are analyzed from various aspects.

[0029] (1) Structural characterization and analysis Figure 1 The XRD pattern of the product obtained in Example 1. 16 The comparison of the standard diffraction peaks of 3H2O revealed that the prepared cathode material had a P21 / m space group structure. At the same time, due to the low concentration of 1-ethyl-3-methylimidazolium chloride and the short stirring time, some characteristic peaks of vanadium pentoxide X-ray diffraction were also present.

[0030] (2) Morphological characterization and analysis Figure 2 The scanning electron microscope images of the products obtained in Examples 1-3 and vanadium pentoxide powder are shown in FIG. Figure 2 a, 2b and 2c correspond to the positive electrode materials prepared in Examples 1, 2 and 3, Figure 2 d is the morphology of vanadium pentoxide powder. Vanadium pentoxide appears as small micron particles, while the vanadium-based materials with imidazolium ion intercalation all show the morphology of nanowires, which can achieve a larger specific surface area, make the electrode and the electrolyte contact more fully, and facilitate the electrochemical reaction process.

[0031] (3) Component characterization and analysis Figure 3 and Figure 4 This is the element distribution diagram of the product obtained in Example 1. The distribution of C and N elements is basically consistent with the distribution of V and O elements, which indicates that 1-ethyl-3-methylimidazolium ions are successfully embedded in vanadium oxide, and the uniform distribution also shows that the embedding of imidazole ions is uniform rather than local. Figure 5 This is the infrared absorption spectrum of the product obtained in Example 1. Characteristic absorption peaks of the imidazole ring and C=N were detected in the spectrum, confirming the existence of imidazole ions and that their functional groups did not change during the embedding process, which can provide active sites for the intercalation of zinc ions and reduce electrostatic effects to improve the diffusion kinetics of zinc ions after embedding.

[0032] (4) Aqueous zinc ion full battery cycle performance test The assembly of the full battery is as follows: the dried vanadium-based positive electrode material and conductive carbon are mixed and ground in a mass ratio of 7:2, and then a polyvinylidene fluoride binder (dissolved in N-methylpyrrolidone) accounting for 1 / 9 of the mass of the above mixture is added to prepare a positive electrode slurry. After stirring for 24 hours, it is coated on carbon paper and then dried overnight to obtain a zinc battery positive electrode sheet. The positive electrode sheet and the zinc foil negative electrode are assembled into a full battery for testing. A whatman fiber diaphragm is used as a diaphragm, a 2 mol / L ZnSO4 solution is used as an electrolyte, a zinc foil electrode is used as a negative electrode, and an imidazole intercalated vanadium-based electrode or a vanadium pentoxide electrode is used as a positive electrode. The electrode surface area is 1cm 2 , the stainless steel sheet is used as the negative electrode gasket, and the full battery is assembled.

[0033] Cyclic charge and discharge tests were carried out at 1 A / g to explore the actual performance of the imidazolium ion intercalated vanadium-based positive electrode. Figure 6 The discharge specific capacity-cycle number curve of vanadium pentoxide and the product obtained in Example 1. In the initial discharge, the discharge specific capacity of the vanadium pentoxide positive electrode is only 73 mAh / g, while the discharge specific capacity of the product obtained in Example 1 is as high as 200 mAh / g, which indicates that the widened interlayer spacing can provide more intercalation sites for zinc ions. There is an activation process in the early stage of the charge and discharge cycle of the vanadium pentoxide positive electrode (water molecules are embedded in the layer, and the capacity increases). It can be seen that its activation requires nearly 100 cycles, while the activation process of the vanadium-based positive electrode material derived from vanadium pentoxide only requires 50 cycles, indicating that the embedding of imidazole ions can accelerate the activation process. In 400 cycles, the discharge specific capacity of the product obtained in Example 1 is significantly higher than that of vanadium pentoxide, and the capacity retention rate is also 13.7% higher than that of vanadium pentoxide.

[0034] (5) Electrochemical performance test of aqueous zinc battery Cyclic voltammetry was performed at 0.4 mV / s. Figure 7The cyclic voltammetry curves of vanadium pentoxide and the product obtained in Example 1, wherein the product obtained in Example 1 has a higher peak current, indicating that the electrochemical kinetics of zinc ion insertion and extraction are enhanced, thanks to the larger interlayer spacing brought by the imidazole cation. During charging, the current peak potential is lower, indicating that the electrostatic shielding effect of the imidazole cation can reduce the battery polarization. Overall, the cyclic voltammetry curve area of ​​the product obtained in Example 1 is much larger than that of vanadium pentoxide, which indicates that the intercalation of imidazole significantly increases the capacity of the battery, which is consistent with the battery cycle test results.

[0035] In summary, the present invention proposes to prepare a vanadium-based positive electrode material with imidazole ion intercalation having a nanowire morphology by a one-pot stirring method. On the one hand, imidazole ions can widen the interlayer spacing of layered vanadium oxides, providing more zinc ion intercalation sites to increase battery capacity, and on the other hand, imidazole ions as interlayer pillars can stabilize the layered structure and reduce the capacity decay rate, and can reduce the electrostatic interaction between zinc ions and oxygen atoms to increase the migration rate of zinc ions between layers. The zinc battery assembled with the positive electrode prepared by this method exhibits excellent electrochemical performance, and exhibits higher capacity and capacity retention characteristics in the cycle performance test, and the current of the cyclic voltammetry method is also larger. This preparation method provides help for the commercial application development of zinc batteries.

[0036] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a vanadium-based positive electrode material, characterized in that: The main steps are as follows: Step (1), placing commercial vanadium pentoxide powder in a beaker, and adding deionized water; Step (2), taking imidazole chloride and adding it into the beaker of step (1); Step (3), adding a magnet to the beaker, and stirring evenly by magnetic force to obtain a mixture; Step (4), filtering the mixture, collecting the solid, and fully drying the solid to obtain a vanadium-based positive electrode material.

2. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: In step (1), the purity of commercial vanadium pentoxide powder is not less than 99%.

3. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: In step (2), the purity of the imidazole chloride is not less than 98%.

4. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: In step (2), the imidazole chloride includes any one or more of 1,3-dimethyl imidazole chloride, 1-methyl-3-ethyl imidazole chloride, and 1-methyl-3-propyl imidazole chloride.

5. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: The concentration of vanadium pentoxide in the product obtained in step (1) is 60-70 g / L.

6. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: The concentration of imidazole chloride in the product obtained in step (2) is 0.5-2 mol / L.

7. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: In step (3), the stirring speed of the magnetic stirring is 600-1000 r / min, and the stirring time is 4 days.

8. The method for preparing a vanadium-based positive electrode material according to claim 1, characterized in that: In step (4), vacuum drying is performed at a temperature of 50-70° C. for 1 day.

9. A vanadium-based positive electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. A zinc battery, characterized in that: Contains the vanadium-based positive electrode material as claimed in claim 9.